Selenium supplementation and ischemia reperfusion injury in rats - Perkins, Anthony; Venardos, Kylie; Harrison, Glenn; Headrick, John (MTT, 2005)
This study examined the effects of selenium supplementation on the activity of glutathione peroxidase and thioredoxin reductase and how this impacted on myocardial function post ischemia reperfusion. Methods: Male wistar rats were fed diets containing 0, 50, 100 and 1000 ug/kg sodium selenite for 5 weeks. Hearts were subjected to Langendorff ischemia and reperfusion, with functional recovery assessed. Heart tissues were assayed for thioredoxin reductase and glutathione peroxidase activity, mRNA expression and for lipid peroxides and protein carbonyls. Results: Hearts from selenium deficient animals were more susceptible to ischemia-reperfusion injury when compared to normal controls (38% recovery of RPP vs 47% RPP) whereas selenium supplementation resulted in improved recovery of cardiac function post ischemia-reperfusion (57% recovery of RPP). There were significantly less lipid peroxides and protein carbonyls in hearts from rats on high selenium diets. The endogenous activity of thioredoxin reductase and glutathione peroxidase and the expression of mRNA for these proteins was increased in selenium supplemented animals. Conclusions: Selenium supplementation reduces oxidative stress and improved cardiac function post ischemia reperfusion in rats.
Keywords: Ka; selenium; anti-oxidant enzyme; ischemia reperfusion injury